2021
DOI: 10.1038/s41598-021-98040-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative malrotation of humerus shaft fracture causes degeneration of rotator cuff and cartilage

Abstract: We hypothesized that postoperative malrotation of humeral shaft fractures can alter the bio-mechanical environment of the shoulder; thus, rotator cuff and cartilage degeneration could be induced. Therefore, we designed an animal experiment to evaluate the impact of malrotation deformities after minimally invasive surgery for humeral fractures on the rotator cuff and cartilage, which has rarely been described in previous studies. Twenty-four New Zealand white rabbits were randomly divided into the sham control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
2
0
1
Order By: Relevance
“…The results of our model analysis are consistent with the above research results, and the peak stress of the scapular glenoid during external rotation in the state of rotational deformity appears in the posterior and inferior part, which is consistent with the epidemiological characteristics that the main wear of shoulder arthritis occurs in the posterior and inferior part of the scapular glenoid and two-thirds of the upper humeral head [ 7 ]. And we also had confirmed through animal experiments that rotational deformity of humeral fracture can lead to degeneration of articular cartilage and rotator cuff, which is consistent with the results of this study [ 6 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of our model analysis are consistent with the above research results, and the peak stress of the scapular glenoid during external rotation in the state of rotational deformity appears in the posterior and inferior part, which is consistent with the epidemiological characteristics that the main wear of shoulder arthritis occurs in the posterior and inferior part of the scapular glenoid and two-thirds of the upper humeral head [ 7 ]. And we also had confirmed through animal experiments that rotational deformity of humeral fracture can lead to degeneration of articular cartilage and rotator cuff, which is consistent with the results of this study [ 6 ].…”
Section: Discussionsupporting
confidence: 90%
“…[ 5 ] prospectively analyzed 45 cases with humeral shaft fracture and found that 27.2% of patients who underwent IMN were present with 20° or more internal malrotation of the humeral head. And We also reported even a much higher incidence of 40.9% in the MIPO group [ 6 ]. Defects in muscle strength, changes in range of motion (ROM) and degenerative arthritis of the shoulder have been reported as consequences of postoperative malrotation of humeral shaft fractures.…”
Section: Introductionmentioning
confidence: 95%
“…17 Although beneficial in these circumstances, the increased rates of malrotation present from IMN remain an area of concern for this procedure because of the long-term effects of malrotation on the glenohumeral joint. 8 In fact, Wang et al 18 used an animal model to study the effects of malrotation on the shoulder and demonstrated that malrotating the humerus by 20 degrees led to early degenerative effects of both the cartilage along with the rotator cuff. In a similar way, Flury and colleagues retrospectively reviewed 34 patients undergoing weber's osteotomy for anteroinferior shoulder instability and found a significant relationship between degree of internal rotation and osteoarthritis disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Zwar sind die Auswirkungen entsprechender Rotationsfehler nicht hinreichend untersucht, dennoch weisen einzelne Studien auf schlechtere funktionelle Ergebnisse und einen eingeschränkten Bewegungsradius hin [61,62,63]. Darüber hinaus können Rotationsfehler zur Degeneration der Rotatorenmanschette und des artikulären Knorpels beitragen [72].…”
Section: Tippunclassified